ENROLMENT PROJECTION AND COST IMPLICATION OF UNIVERSAL BASIC EDUCATION IN NIGERIA - Igbineweka, V. O.; Adeyemi, J. K. (Sokoto Educational Review, 2015)
The paper evaluated implementation of the Universal Basic Education (UBE) scheme for the first ten years of implementation, 2002-2012. Pupil enrolment for the period was projected and the cost implication of implementing the scheme estimated to guide government assess its ability to continue the implementation of the scheme, review its strategies of implementation or even abandon the scheme like the previous experiment with UBE scheme. The two research questions raised for the study were answered using documentary analysis, models and descriptive statistics. The result of analysis showed that over 46 million children would have been enrolled in schools and N52.9 billion spent annually if the scheme had been effectively implemented. The sight of basic school-going aged children at motor parks, markets and hawking along major streets during school hours suggests that the implementation of the scheme has not effective. It was therefore recommended among others that government should concentrate only on the supply and management of basic education in order to garner adequate funds to sustain its implementation and, allow private individuals and non-governmental organizations to supply and manage other levels of education.